Clinical practice preferences of Australian and New Zealand practitioners in the implant management of the edentulous mandible - James Dudley; Fiza Mughal (Wolters Kluwer Medknow Publications, 2020)
Introduction: Mandibular edentulism remains a widespread health burden with a variety of available treatment modalities, but without an accepted single best practice approach. The purpose of the present study was to survey clinical practice preferences of Australian and New Zealand practitioners in the management of patients with edentulous mandibles with a specific focus on the use of dental implants. Materials and Methods: A questionnaire comprising thirty questions was developed and administered online via a unique web link sent to all known Australian and New Zealand general dental and specialist professional membership bodies. Results: Responses received from the members of five of the ten membership bodies constituted 7.35% overall response rate. Respondents who had undertaken implant training and were involved in implant treatment of the edentulous mandible totaled 65.5%. The pattern of referral to specialists for surgical implant placement varied according to the type of prosthesis being constructed. Of 111 respondents, 72% preferred two implants for mandibular implant overdentures (MIODs), whereas 97% of 98 respondents preferred four or more implants for a mandibular fixed complete implant denture. The main reasons for choosing MIOD instead of fixed complete implant denture were cost, patient preference, and available jaw bone. Conclusions: The highest level of education in implant dentistry varied significantly between respondents and was potentially reflected in the wide variety of reported treatment approaches. Even within a specific implant prosthesis type, there was no universally accepted modality of management. Future research should focus on alternative survey strategies for obtaining important data representative of the total practicing population.